The Interrelationship Between Faculty Job Satisfaction, Service Quality And Student Satisfaction: The Case Of VNU - International School - Pham, Lien; Do Thi Hoang, Xuyen (VNU Journal of Science: Policy and Management Studies; Vol 33 No 2, 2017)
This research attempts to evaluate the interrelationship between employee satisfaction, service quality, and customer satisfaction in an educational organization. Specifically, this study explores three major relationships: (1) the relationship between influential factors of job satisfaction and faculty satisfaction; (2) the relationship between faculty satisfaction and service quality; and (3) the relationship between service quality and customer satisfaction. The study uses data collected from the questionnaire survey with 167 responses. As a result, there is a positive relationship between employee satisfaction and service quality and in turn service quality has positive effect on student satisfaction. Three out of six variables relating to job satisfaction (including Salary and Fringe benefits, Recognition, and Communiation) have influential relationship with lecturer job satisfaction in the linear regression analysis. And all the five factors of training service quality have positive relationships with student satisfaction. The paper also gives some recommendations for the school to improve its policies and working environment to enhance lecturer job satisfaction as well as service quality and student satisfaction level.